The Influence of Utilitarian Value and Hedonic Value on Loyalty with Consumer Satisfaction As Mediation on The Consumer "Society Coffe House" - Farhah, Nida Umi; Warsito, Chandra; Ab. Wahab, Norailis; Zuhdi, Tohir (Ijtimā iyya Journal of Muslim Society Research, 2025)
The research aims to analyze the influence of utilitarian value and hedonic value on consumer loyalty with consumer satisfaction as mediation in consumer coffee shops. A product's utilitarian and hedonic value is significant because it affects consumers until the emergence of brand satisfaction. Utilitarian values such as usability, the function of a product, and the hedonic value of a product, such as luxury pleasure, become the values of a product that affect consumer satisfaction. The analytical methods used to test relationships between variables are Partial Least Squares Analysis, hypothesis testing using the t-test, and moderation testing using the Variance Accounted For method—sample number of 100 coffee shop customers in Indonesia.The finding of this study is that the consumer satisfaction factor can mediate the relationship between utilitarian value, hedonic value, to customer loyalty. This study found that utilitarian factors of value, hedonic value, and consumer satisfaction are determining variables in increasing consumer loyalty in coffee shops. The thing that can be done is to improve the quality of products to be better and different from other cafes, create conditions that are entirely different and not obtained from elsewhere when consumers enjoy coffee, and continue to provide the best service so that consumers will continue to want to consume coffee. Until now, no research has tested consumer satisfaction as a mediation variable in conjunction with utilitarian value variables and hedonic value to customer loyalty to coffee shops in Indonesia